Iqbal’s Ego Philosophy and Its Importance in Awakening Man’s Spirituality Falsafah Ego Iqbal dan Kepentingannya dalam Kebangkitan Kerohanian Manusia - Abdul Razak, Mohd Abbas (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
Abstract History reveals the fact that the coming of modernity and secularism has allured modern man towards a materialistic concept of life, ignoring his spiritual needs in respect of his role as the vicegerent of God. This predicament has not only marred man’s relationship with God but has also failed him toward understanding his true nature and mission in life. The large segment of humanity today is on the brink of losing its human and spiritual values, resulting in severe environmental degradation, racism, terrorism, war, poor mental health, and other psychopathological illnesses. This paper intends to explore and draw out conclusions from the philosophical thoughts of Muhammad Iqbal (1877-1938) with regard to his ego philosophy that explains man’s relationship with God, community and the universe (flora and fauna). Lessons drawn out from Iqbal’s ideas can be of great use in awakening man’s spirituality and improving his quality of life by establishing a harmonious relationship with God, environment and fellow human beings. Keywords: Iqbal, Ego Philosophy, Man, Spirituality. ******************************** Abstrak Sejarah menunjukkan satu hakikat bahawa kedatangan kemodenan dan sekularisme telah menarik manusia moden ke arah konsep hidup materialistik, mengabaikan keperluan rohaninya berkenaan dengan peranannya sebagai khalifah Allah. Keadaan ini bukan sahaja mencemarkan hubungan manusia dengan Tuhan tetapi telah membuat dirinya gagal untuk memahami sifat sebenarnya dan misinya dalam hidup. Segmen besar manusia hari ini berada di ambang kehilangan nilai-nilai kemanusiaan dan kerohanian, menyebabkan kemusnahan alam sekitar yang teruk, sifat perkauman, keganasan, peperangan, kesihatan mental yang lemah, dan penyakit-penyakit psychopathological. Karya ini bertujuan untuk meneroka dan menarik keluar kesimpulan dari pemikiran falsafah Muhammad Iqbal (1877-1938) dengan mengambil kira falsafah ego beliau yang menerangkan hubungan manusia dengan Tuhan, masyarakat dan alam semesta (flora dan fauna). Pengajaran yang boleh diterima dari fikiran Iqbal boleh menjadi amat berguna dalam kebangkitan kerohanian manusia dan meningkatkan kualiti hidup beliau dengan mewujudkan hubungan yang berharmoni dengan Allah, alam sekitar dan sesame manusia. Kata Kunci: Iqbal, Falsafah Ego, Manusia, Kerohanian.